como resolver esse logaritmo ??
log3 (x+2) - log3 (x-2) = log3^3
ctsouzasilva:
O que se quer saber ? Falta a pergunt.
Respostas
respondido por:
2
Resposta:
x = 28/13
Explicação passo-a-passo:
log₃(x + 2) - log₃(x - 2) = log₃3
Primeiramente se deve ter:
x + 2 > 0 ⇒ x > -2 e x - 2 > 0 ⇒ x > 2 Intersedendo , dá x > 2
Resolvendo
log₃(x + 2) - log₃(x - 2) = log₃3
log₃(x + 2)/(x - 2) = log₃3
(x + 2)/(x - 2) = 3³
27(x - 2) = x + 2
27x - 54 = x + 2
27x - x = 2 + 54
26x = 56
x = 56/26
x = 28/13 (é maior que 2, então serve).
Perguntas similares
5 anos atrás
5 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás